Respostas
respondido por:
1
Vamos lá:
A)f(3)
f(x)=5x+6
f(3)=5.3+6
f(3)=15+6
f(3)=21
B)f(0)
f(x)=5x+6
f(0)=5.0+6
f(0)=+6
C)f(2)
f(2)=5.2+6
f(2)=10+6
f(2)=16
D)f(-1)
f(-1)=5.(-1)+6
f(-1)=-5+6
f(-1)= +1
Espero ter te ajudado!
A)f(3)
f(x)=5x+6
f(3)=5.3+6
f(3)=15+6
f(3)=21
B)f(0)
f(x)=5x+6
f(0)=5.0+6
f(0)=+6
C)f(2)
f(2)=5.2+6
f(2)=10+6
f(2)=16
D)f(-1)
f(-1)=5.(-1)+6
f(-1)=-5+6
f(-1)= +1
Espero ter te ajudado!
germano125:
obrigado
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás